Tapping into the collective wisdom of community to make great products - Libert, Barry ([FTPress Delivers], 2010)
This Element is an excerpt from We Are Smarter Than Me: How to Unleash the Power of Crowds in Your Business (9780132244794) by Barry Libert and Jon Spector. Available in print and digital formats. How your customers can help you design better products and services than you could ever create by yourself! There's much to be said for tapping the collective wisdom of a community for product ideas. It gives customers a vested interest in the results and helps guarantee that they'll like what they've created. Many companies have pioneered product development by people not on their payroll. They range from food giants to the inventors of a popular virtual world that has confounded the skeptics ...
Cover title. - Imprint from cover p. [3]. - Excerpted from: We are smarter than me, by Barry Libert and Jon Spector. Cf. resource description page (viewed March 4, 2010)
Keywords: Strategic alliances (Business); Social participation -- Economic aspects; Customer relations; Customer services; Marketing research; Alliances stratégiques (Affaires); Participation sociale; Aspect économique; Service à la clientèle; Marketing; Recherche; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior